How do sexual and gender minority people acquire the capability for suicide? Voices from survivors of near-fatal suicide attempts - Kirsty A. Clark; Travis Salway; Erin M. McConocha; John E. Pachankis (Elsevier, 2022)
Despite well-documented disparities by sexual and gender minority (SGM) status in suicide attempt and mortality rates, few studies have investigated the lived experiences that contribute to SGM people's disproportionate risk of suicide. Having a history of at least one near-fatal (or medically serious) suicide attempt serves as a proxy for suicide mortality, but no known study has involved SGM people who have made such an attempt. Ideation-to-action theories of suicide posit that individuals acquire the capability for suicide through repeated exposure to painful and provocative events - namely, traumatic, threatening, and risky experiences - that can diminish the pain and fear of death. Yet whether identity-specific features of acquired capability for suicide contribute to SGM people's disproportionate risk of suicide remains unknown. Drawing upon interviews with 22 SGM people who experienced a recent near-fatal suicide attempt, the current study sought to identify specific determinants of how SGM individuals acquire the capability to kill themselves, a potentially powerful, and modifiable, pathway to suicide. Results identified three SGM-specific contributors to the acquired capability for suicide: (1) identity invalidation during developmentally sensitive periods of childhood and adolescence that left participants feeling erased, invisible, and, in some cases, non-existent; (2) normalization of suicide within SGM social networks that increased acceptability and reduced the fear of suicide; and (3) structural stigma and SGM community trauma as habituating sources of pain that engendered feelings of exhaustion and positioned suicide as a reprieve from pervasive anti-SGM norms. This study demonstrates that dominant suicidology theories might need to be refined to account for the stigma-related determinants of SGM suicide. Further, this study reinforces the importance of qualitative methods for understanding the lived experience of suicide and calls for SGM-specific suicide prevention efforts to respond to stigma to support those SGM people who contemplate suicide.